CHEMICAL POST-PROCESSING METHODS FOR ENHANCING SURFACE PROPERTIES OF PARTS FABRICATED BY ADDITIVE MANUFACTURING: A REVIEW - (:unkn) unknown (YILDIZ TECHNICAL UNIV, 2020)
Additive manufacturing is a rapidly developing field due to the production of complex geometry parts with rapid prototyping with a wide range of applications. In addition to the great advantages, Additive manufacturing produces components with relatively poor surface quality. For this reason, post-processing operations are inevitable to have ready-to-use products. Various post-processing operations including mechanical, chemical and thermal are being implemented to components fabricated by additive manufacturing processes. The purpose of this article is to review chemical post-processing operations and their effect on surface enhancement. This review study shows that chemical post-processing operations have great potential to improve surface aspects of components fabricated by additive manufacturing.
Keywords: Additive manufacturing; chemical post-processing; 3D printing; surface treatment; ROUGHNESS; SCAFFOLDS; ABS